Crystal structure of elvitegravir Form II, C23H23ClFNO5. Issue 1 (March 2023) - Kaduk, James A.; Gates-Rector, Stacy; Blanton, Thomas N.
Abstract : The crystal structure of elvitegravir Form II has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional theory techniques. Elvitegravir Form II crystallizes in space group P 21 (#4) with a = 11.54842(7), b = 14.04367(5), c = 13.33333(8) Å, β = 90.0330(6)°, V = 2162.427(14) Å 3, and Z = 4. The crystal structure consists of alternating layers of parallel molecules perpendicular to the b -axis. The mean planes of the oxoquinoline ring systems in molecules 1 and 2 are 1(22)-1 and -1(22)1. Between the stacks are layers of the halogenated phenyl rings. These exhibit herringbone stacking. In each molecule, the carboxylic acid group forms a strong intramolecular O–H⋯O hydrogen bond to the nearby carbonyl group. The hydroxyl group of each molecule forms a strong hydrogen bond to the carbonyl group of the carboxylic acid of the other molecule. These O–H⋯O hydrogen bonds link the molecules into dimers, with a graph set R2, 2(18) > a > c . The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™ (PDF®).